The development and comparison of two polarimetric calibration techniques for ground-based circularly polarized radar system - Izumi Y.; Demirci S.; Baharuddin M.Z.; Waqar M.M.; Sumantyo J.T.S. (Electromagnetics Academy, 2023)
Circular polarization; Polarimeters; Radar; Radar measurement; Radar systems; Reflection; Synthetic aperture radar; Calibration method; Calibration techniques; Circularly polarized; Linearly polarized; Polarimetric calibration; Polarimetric radars; Scattering matrices; Theoretical values; Calibration